Pelatihan Pembukuan Sederhana Kepada Pelaku Usaha di Desa Wisata Cibeber, Purwakarta, Indonesia - Ratnaningtyas, Heny; Wicaksono, Haryo; Annisa, Annisa (Jurnal Pemberdayaan Pariwisata, 2025)
This community engagement program was carried out to address financial management issues faced by small business owners in Cibeber Village, Purwakarta, a developing tourist village. The program aimed to enhance participants’ ability to perform simple bookkeeping to support better financial decisions. A participatory approach was adopted, involving business owners in preparation, training, and evaluation stages. Data were collected through interviews and observations with 25 participants. The training showed significant improvements: daily transaction recording increased from 20% to 72%, possession of financial records rose from 16% to 68%, and separation of business and personal expenses improved from 24% to 76%. Several participants also began using simple digital tools such as Google Sheets and mobile bookkeeping applications. Feedback through questionnaires showed unanimous agreement that the program was beneficial, practical, and well-delivered. This indicates that the method aligned well with the real needs and challenges of the community. The program effectively empowered local entrepreneurs by improving their financial literacy and encouraging the adoption of digital tools. For future community empowerment initiatives, it is suggested to provide continuous assistance and follow-up training in digital bookkeeping to ensure sustainability and support the transition toward smarter, technology-driven financial practices in rural enterprises . Keywords: simple bookkeeping training, economic empowerment, financial management